“Estou pensando sempre em fazer a vontade dos outros, mas os outros não pensam nunca em fazer a minha vontade”: a trabalhadora doméstica negra em Lygia Fagundes Telles (1965-1989) - Novaes, Diego Amorim (2021)
Our objective is to investigate the construction of black domestic workers characters in the works of the São Paulo writer Lygia Fagundes Telles (1923-present). We work on four of the author's works: the short story Antes do Baile Verde (1965), the novel As Meninas (1973), the tale Noturno Amarelo (1977) and the novel As Horas Nuas (1989). As a theoretical tool, we use the notion of black feminism of the intersectionality through its articulation with the categories of class, gender and race (AKOTIRENE, 2019). The main theorists who support us are Silvia Federici (2019) and Lélia Gonzalez (2018a,b) giving us a feminist-Marxist perspective on domestic work and a critique of its race in Brazil. The notion of capitalist domesticity, present in Perrot (1988) and Federici (2019), is also essential to our work. Telles builds her characters with the aim of destroying this domestic and therefore subvert the image of the happy nuclear family headed by a man. By inverting this social pyramid of the domestic, the author, however, does not exempt herself from marking her characters with the attributes that oppress them in the real world.